(untitled) (Interdisciplinary Research in Education, 2022)
This study explores the changing contexts of the globalized world and their impact on the learning strategies in higher education classrooms. Globalization has influenced educational philosophy and classroom practices all over the world. The forces associated with globalization have altered the context in which educators operate, and intensely changed ones experience in both formal and informal education. The purpose of this study was to examine the quality of existing online education courses that utilize the internet as the primary instructional delivery method. The focus of this study was to find out students’ perceptions on the impact of online learning on MPhil level classes in TU Kirtipur. It highlights the challenges facing in use of ICT in higher education of in Nepal. Problems such as lack of resources (viz. qualified teachers, hardware, software, electricity and poor project implementation strategies militate against these efforts. This study recommends university authority should help to facilitate skilled manpower, stabilized electricity supply, hardware resources and software resources to enhance the use of ICT in higher education classrooms. It is argued that, to realize the policy in practice, more sustainable mechanisms need to be developed to provide ICT facilities for teachers and to train them how to use ICT in teaching activities. The study also includes some of the implications to connect on virtual classroom used in an online learning environment affected students’ active participation in learning activities.